Direct resin composite restoration of maxillary central incisors using a 3D-printed template: two clinical cases - Juan Xia; Yinghua Li; Dongping Cai; Xilin Shi; Shiyong Zhao; Qianzhou Jiang; Xuechao Yang (BMC, 2018)
Abstract Background Three-dimensional (3D) printing technology is used widely in dentistry for applications including implant surgery, oral and maxillofacial surgery, orthognathic surgery, endodontics and prosthodontics. Using a 3D-printed template makes performing the repair procedure faster and more convenient. The aesthetic restoration of anterior teeth can recover facial beauty, enhance speaking and chewing functions and improve the quality of life of the patient. Case presentation This article describes two kinds of clinical cases including fractured teeth and dental caries. In both, a 3D-printed template was used for direct resin composite restoration of maxillary central incisors. A 3D-printed template was built using the following 3-step process: data acquisition was conducted via intra-oral scanning, virtual modeling was performed using an imaging process, and manufacturing was performed using a 3D printer. Aesthetically restoring the maxillary incisors with the assistance of the 3D-printed template achieved the anticipated results, and the patients were very satisfied with the effect. Conclusions The direct resin composite restoration of maxillary central incisors using a 3D-printed template represents a rapid, convenient, aesthetic and functional option for treating maxillary central incisors. A 3D-printed template is therefore an acceptable and reliable alternative to traditional direct composite restoration of maxillary central incisors including fractured teeth and dental caries.